Devices and Methods for Measuring of the Ambient Air Dust. Short Review - N. I. Mukhurov; A. A. Khodin; Y.-J. Kim (Приборы и методы измерений)
The main characteristics of airborne micro/nanoparticles, their impact on human health and air quality standards are presented. International standards classify microparticles by size (PM10, PM2.5, PM1, UFP), establish maximum allowable concentrations and control methods. Particular attention is paid to carbonand virus-containing microparticles control. To monitor the air environment in enclosed spaces and in transport, the portable sensors of micro-, nanoparticles are required with the ability to classify them by size and electrophysical characteristics.Detection of microparticles includes the sorting of particles entering the sensor by size and material type, subsequent actual detection of particles of the same kind, with subsequent classification by size, electrical and morphological characteristics. Separation of nanoand microparticles by size before detection improves the sensitivity and selectivity of the detector both in size and material. The virtual impactor and dielectrophoresis method are considered for integration in a Lab-on-Chip type sensor. Detection of microparticles is performed by separating the dispersed phase from the aerosol followed by the analysis, or directly in the air flow. The classification of detection methods according to speed and functionality is given. Among the methods allowing detection of micrometer and submicrometer size particles, the most suitable for miniaturization and serial production of Lab-on-Chip sensors are the multi-wavelength photoelectric, MEMS, and capacitor elements.The microelectromechanics, microfluidics and microoptics technologies make it possible to create portable sensor systems of the Lab-on-Chip type to detect particulates matter of micrometer and submicrometer size. A micro-, nanoparticles detector prototype based on alumina technology using MEMS elements for a compact Lab-on-Chip type sensor is presented. The proposed design for multifunctional portable detector of airborne micro/nanoparticles is prospective for industry, transport, medicine, public and residential buildings applications.